2008
DOI: 10.1016/j.cgh.2008.06.024
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Risk Factors and Historical Trends in Metronidazole Failure for Clostridium difficile Infection

Abstract: Background & Aims-Recent studies of C. difficile infection (CDI) indicate a dramatic increase in metronidazole failure. The aims of this study were to compare current and historical rates of metronidazole failure and identify risk factors for metronidazole failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…A recent prospective study of hospitalized patients (without IBD) showed a high failure rate with metronidazole treatment for C. diffi cile in patients who had been recently treated with cephalosporins, in those who were positive for C. diffi cile on admission, and in those transferred from another hospital. In such cases, therefore, vancomycin should be considered as the preferred initial antibiotic ( 254 ).…”
Section: The Patient With Severe Colitis Refractory To Maximal Oral Tmentioning
confidence: 99%
“…A recent prospective study of hospitalized patients (without IBD) showed a high failure rate with metronidazole treatment for C. diffi cile in patients who had been recently treated with cephalosporins, in those who were positive for C. diffi cile on admission, and in those transferred from another hospital. In such cases, therefore, vancomycin should be considered as the preferred initial antibiotic ( 254 ).…”
Section: The Patient With Severe Colitis Refractory To Maximal Oral Tmentioning
confidence: 99%
“…infection with the epidemic nAP-1 strain was not associated with metronidazole failure in endemic cDi. 22 continued use of non-C. difficile antibiotics after diagnosis of cDi, concomitant prescription of antacid medications, and older age were significantly associated with increased risk of recurrent cDi. 15 Evidence for the association between C. difficile and the use of PPis is unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Table 1 shows the main characteristics of the included studies. The majority of the studies were conducted in North America (n = 26) [13,14,[16][17][18][19][20]23,[25][26][27]31,33,34,38,40,41,[43][44][45][46][47][48][49][50][51], whilst 7 were conducted in Europe (mainly in the UK) [21,22,[28][29][30]32,35]. One more study included patients from North America and the UK [15], four from Asia (South Korea and Taiwan) [36,37,39,42] and one from Argentina [24].…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Amongst 1669 articles retrieved through electronic and reference list searches, 39 articles were selected as evaluable for inclusion in the systematic review . More specifically, 7 RCTs (1214 patients) [13][14][15][16][17][18][19], 11 prospective studies (1057 patients) [20][21][22][23][24][25][26][27][28][29][30] and 21 retrospective studies (4734 patients) were identified. A total of 7005 patients were studied.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%